Milk Production and Morphometrics Derived from Digital Images of Friesian and Holstein Cows in Different Lactation Periods - M. A. F. Nasution; A. Atabany; B. P. Purwanto; W. A. Zahra (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2024)
This study was conducted to analyze milk production and morphometrics derived from digital images of Friesian and Holstein cows in smallholder farms located in Pondok Rangon, Lembang, and Cibungbulang Bogor in different lactation periods. The morphometric parameters measured in this study included body length, height, chest girth, and body weight. The findings indicated that Holstein cows exhibited greater body length, height, chest girth, and body weight compared to Friesian cows across all farms. Milk production in Friesian cows remained relatively stable from lactation periods one to three. Additionally, body length, height, chest girth, and body weight were found to influence the milk production of both Friesian and Holstein cows. Cows with longer body lengths, greater heights, higher body weights, and wider chest girths tended to produce more milk. Chest girth and weight emerged as the primary factors influencing milk production in Friesian and Holstein cows, while height, body length, and lactationperiod also played significant roles.